Fake News, Epistemic Coverage and Trust. Issue 4 (8th May 2021) - Ryan, Shane
Abstract: This article makes the case that a deficit or absence of trust in media sources to report on newsworthy items facilitates acceptance of fake news. The article begins by identifying the sort of fake news that is of interest for the purposes of this article. Epistemic coverage is then explained—in particular, how an individual's expectations about their epistemic environment can lead them to accepting or rejecting claims. The article explains that when an individual believes that mainstream media report on what is deemed newsworthy, it follows that an individual will have grounds to dismiss a newsworthy claim that has not been reported upon—such as a claim made by fake news. Trust—which has both a believed competence requirement and a believed goodwill requirement—is then discussed as part of this explanation. The article concludes with a discussion of the implications of the argument for regulating mainstream media.